Pemanfaatan Media Gambar dalam Proses Pembelajaran Micro Teaching - Flaviani Resiansi Koy Mali; Lenisia Hoar Asa; Nofrianus Nahak; Emanuel Jekson Abela; Oktoviana Rika (Jurnal Pendidikan Dirgantara, 2025)
This study aims to describe the use of visual media in the microteaching learning process. The main focus of the research is to understand how visual media is utilized in student teaching practice and its impact on their teaching skills. This research employs a qualitative approach with a descriptive method. The research subjects are education students who are currently enrolled in a microteaching course. Data were collected through observation, interviews, and documentation. The results of the study indicate that the use of visual media in microteaching enhances the clarity of material delivery, attracts the attention of simulated students, and assists students in developing more structured learning strategies. Visual media also encourages students’ creativity in designing engaging and communicative learning activities. Therefore, the use of visual media in microteaching contributes positively to improving the pedagogical competence of prospective teachers.